2014
DOI: 10.15282/ijame.9.2013.27.0149
|View full text |Cite
|
Sign up to set email alerts
|

Edge Length Effect of Bluff Bodies on Flow Structure

Abstract: This study investigates the flow structure around two identical triangles placed side by side, through experiment. Its goal is to investigate the effects of the edge length of the bluff bodies on flow structure. The flow characteristics are performed for a Reynolds number range varying from 5.000 to 10.000 under steady state conditions, and the flow was assumed to be two-dimensional. The flow characteristics around the bluff bodies were analyzed using particle image velocimetry (PIV) velocity measurement techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The vortexes in these three regions are created due to the flow separation. The velocity of the air and the shape of truck affect the size of these vortexes [11]. A low-pressure is created behind the trailer when the separation occurs and the air is sucked into the Region 3 from all the sides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vortexes in these three regions are created due to the flow separation. The velocity of the air and the shape of truck affect the size of these vortexes [11]. A low-pressure is created behind the trailer when the separation occurs and the air is sucked into the Region 3 from all the sides.…”
Section: Resultsmentioning
confidence: 99%
“…Despite so many advances in the numerical methods, the accurate and valid simulation of flow around the trucks is not simple regarding to the different phenomena in the turbulent flow field as well as the geometric complexities. Flow separation and vortex formation occur in the turbulent flow around the trucks [10,11]. Thus, the three-dimensional simulation of this kind of problems requires strong meshing tool, reliable solution algorithms, and appropriate computer resources.…”
Section: Introductionmentioning
confidence: 99%
“…The working principle involves electrification of the propellant (gas or water), which can then be directed by a magnetic field, pushing the vehicle in the opposite direction. MHD is used to stabilize a flow against the transition from laminar to turbulent flow [7]. The effect of the magnetic field on the viscous incompressible flow of electrically conducting fluid is important in many applications, such as extrusion of plastics in the manufacture of rayon and nylon, purification of crude oil, pulp, the paper industry, textile industry and in different geophysical cases, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The average local Nu number increased as Reynolds number increased. Manay et al 24 studied the effect of the spacing between equilateral dual triangular bodies symmetrically placed into a channel axis under steady state conditions on heat transfer and fluid characteristics by using artificial neural networks (ANN). The results indicated that the local Nusselt number and skin friction coefficient took a local maximum at the placed position of the upstream body, and at the placed position of the downstream body.…”
Section: Introductionmentioning
confidence: 99%